EPI-CT: in vitro assessment of the applicability of the γ-H2AX-foci assay as cellular biomarker for exposure in a multicentre study of children in diagnostic radiology. (August 2015) - Vandevoorde, Charlot; Gomolka, Maria; Roessler, Ute; Samaga, Daniel; Lindholm, Carita; Fernet, Marie; Hall, Janet; Pernot, Eileen; El-Saghire, Houssein; Baatout, Sarah; Kesminiene, Ausrele; Thierens, Hubert
Abstract Purpose: To conduct a feasibility study on the application of the γ-H2AX foci assay as an exposure biomarker in a prospective multicentre paediatric radiology setting. Materials and methods: A set of in vitro experiments was performed to evaluate technical hurdles related to biological sample collection in a paediatric radiology setting (small blood sample volume), processing and storing of blood samples (effect of storing blood at 4°C), the reliability of foci scoring for low-doses (merge γ-H2AX/53BP1 scoring), as well as the impact of contrast agent administration as potential confounding factor. Given the exploratory nature of this study and the ethical constraints related to paediatric blood sampling, blood samples from adult volunteers were used for these experiments. In order to test the feasibility of pooling the γ-H2AX data when different centres are involved in an international multicentre study, two intercomparison studies in the low-dose range (10–500 mGy) were performed. Results: Determination of the number of X-ray induced γ-H2AX foci is feasible with one 2 ml blood sample pre- and post-computed tomography (CT) scan. Lymphocyte isolation and fixation on slides is necessary within 5 h of blood sampling to guarantee reliable results. The possible enhancement effect of contrast medium on the induction of DNA DSB in a patient study can be ruled out if radiation doses and the contrast agent concentration are within diagnostic ranges. The intercomparison studies using in vitro irradiated blood samples showed that the participating laboratories, executing successfully the γ-H2AX foci assay in lymphocytes, were able to rank blind samples in order of lowest to highest radiation dose based on mean foci/cell counts. The dose response of all intercomparison data shows that a dose point of 10 mGy could be distinguished from the sham-irradiated control (p = 0.006). Conclusions: The results demonstrate that it is feasible to apply the γ-H2AX foci assay as a cellular biomarker of exposure in a multicentre prospective study in paediatric CT imaging after validating it in an in vivo international pilot study on paediatric patients.